DISCUSSING SIMPLE FILM THAT REPRESENTS NARRATIVE TEXT TO IMPROVE STUDENTS SKILLS IN ENGLISH - Ashari Hasibuan (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to find out the effectiveness of discussinga film to improve students' speaking skills in English. The main focus of the activity is discussing simple film that represents narrative text to improve speaking skills in KelasIX-1 in SMP Negeri 1 Padangsidimpuan. This is a qualitative study, conducted online in the form of Classroom Action Research (CAR) with 25 students as participants and the researcher himself as participant observer. The research did in two cycles and data colleting did by observationand document analysis. The findings then analyzed and described qualitatively based on the theories proposed in this study. The study then proves the following points. Watching and discussing films that represents narrative text significant to improve students' speaking skills in KelasIX-1 in SMP Negeri 1 Padangsidimpuan. Discussing films develops students' ability regarding critical thinking. This study proves that film as teaching media is very effective for learning speaking and listening and also very interesting and entertaining. However, online teaching requires maximal effort from teacher to motivate students and technical problem regarding internet facilitation still contributes some obstacles in performing an online teaching. Thus, further study regarding the issues need to be conducted in a broader scale for better findings.